Discoveries of the specific expression of lncRNAs and mRNAs in hippocampus of rats after traumatic brain injury. Issue 2 (28th June 2021) - Li, Juan; Pan, Yuan‐Tao; Chen, Jun‐Jie; Wang, Yi; Zhou, Hong‐Su; Huang, Xue‐Yan; Liao, Shi‐Xia
Abstract : Objects: Explore the relationship between the neural function deficit and the changes of lncRNA and mRNA in hippocampus after traumatic brain injury (TBI) in rats. Methods: Twenty male rats weighted 200‐240 grams were randomly divided into sham group and TBI group. Neurologic severity score (NSS) was performed after operation, and the hippocampus of rats was collected for long non‐coding RNAs (lncRNAs), mRNAs microarray detection, real‐time quantitative PCR Detecting System (Q‐PCR), western blot (WB) detection, and serum biochemical detection. Results: The NSS score of the TBI group was significantly higher than the sham group. Compared with the sham group, 270 lncRNAs changed in the TBI group, of which 224 were up‐regulated and 46 were down‐regulated. Among up‐regulated lncRNAs, mRNAs were distributed in upstream of 22 lncRNAs, downstream of 17 lncRNAs, overlapping regions of 48 lncRNAs, and antisense chains of 21 lncRNAs. Among down‐regulated lncRNAs, mRNAs were distributed in upstream of 6 lncRNAs, downstream of 3 lncRNAs, overlapping regions of 10 lncRNAs, and antisense chains of 8 lncRNAs. Compared with the sham group, 1054 mRNA changed in the TBI group, of which 921 mRNA were up‐regulated and 133 mRNA were down‐regulated. The expression changes of ENSRNOT000063054, ENSRNOT000052790, ENSRNOT00000054410, ENSRNOT000063242, and ENSRNOT000069411 IncRNA regulate the expression of Top2a, RT1‐CE11, Papss2, Stk32a, and Grid2 gene. Conclusion: The present study detected the differential expression of lncRNAs and mRNAs in hippocampi of rats subjected to TBI, and discussed their relation, primarily.